1998
DOI: 10.1063/1.121081
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic and ferromagnetic resonance imaging with a tip-on-cantilever magnetic resonance force microscope

Abstract: A magnetic resonance force microscope with a “tip-on-cantilever” configuration was used to compare imaging characteristics of paramagnetic and ferromagnetic samples. Three-dimensional electron paramagnetic resonance (EPR) imaging of diphenylpicrylhydrazil (DPPH) particles was accomplished by scanning the sample in two dimensions while stepping an external field. The EPR force map showed broad response reflecting the size and shape of the sample, allowing a three-dimensional real-space magnetization image to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 13 publications
2
60
0
Order By: Relevance
“…47 Even the first demonstration of "magnet on tip" MRFM, though a remarkable development, employed a large enough magnetic tip that the gradient was not much larger than in early experiments. 48 By gluing magnets as small as 5 m to commercial silicon nitride cantilevers and operating the cantilevers within a few tens of nanometers of a surface, Bruland et al 49 were able to detect electron spin resonance using magnetic field gradients as large as 2.5ϫ 10 5 T / m. The sensitive slice in these experiments was only a nanometer thick, on the order of molecular dimensions. Remarkably, at a temperature of 77 K, Bruland et al achieved a magnetic moment sensitivity of ϳ200 e / ͱ Hz.…”
Section: A Sensitivitymentioning
confidence: 98%
See 3 more Smart Citations
“…47 Even the first demonstration of "magnet on tip" MRFM, though a remarkable development, employed a large enough magnetic tip that the gradient was not much larger than in early experiments. 48 By gluing magnets as small as 5 m to commercial silicon nitride cantilevers and operating the cantilevers within a few tens of nanometers of a surface, Bruland et al 49 were able to detect electron spin resonance using magnetic field gradients as large as 2.5ϫ 10 5 T / m. The sensitive slice in these experiments was only a nanometer thick, on the order of molecular dimensions. Remarkably, at a temperature of 77 K, Bruland et al achieved a magnetic moment sensitivity of ϳ200 e / ͱ Hz.…”
Section: A Sensitivitymentioning
confidence: 98%
“…They concluded that the tip magnetic moment must be minimized and that the applied polarizing field must be highly uniform. 131,132 Magnet-on-tip cantilever detection of ESR was demonstrated by Wago et al 48 These experiments, though successful, indicated that operating the magnetic-tipped cantilever in high magnetic field also leads to a catastrophic increase in cantilever friction. This effect was not present in the magneton-cantilever ESR experiment of Bruland et al because the polarizing field was zero and the tip field was used to polarize the sample.…”
Section: G From Sample-on-cantilever To Magnet-on-cantilever Experimmentioning
confidence: 99%
See 2 more Smart Citations
“…following Ref. [48], where a Nickel sphere was attached to the cantilever, whose Q could then be changed by 3 orders of magnitude by applying a magnetic field.…”
Section: Non-gaussian State Via Interaction With Single Photons and Pmentioning
confidence: 99%